Topographic And Anatomical Pathways Of Tumor Dissemination In The Female Reproductive Organs - Jalolov Oybek Kamoliddinovich (Genius Journals, 2025)
The anatomy of the female pelvis and reproductive organs constitutes a highly complex topographic–anatomical system that plays a pivotal role in understanding the clinical behavior and dissemination patterns of malignant tumors. Accurate knowledge of pelvic anatomy is of particular importance in gynecologic oncology, where surgical strategy, the extent of lymphadenectomy, identification of metastatic routes, and prognostic assessment are directly influenced by individual variations in vascular supply, lymphatic drainage, organ syntopy, and fascial and cellular compartments.
Keywords: uterus; vagina; blood vessels